The impact of academic stress on psychological well-being: A case study of international students at Northeast Normal University - Bong Kim Ki; San Su Su San; Nuruddin Ahmed Masud; MST Taherun Nesa Subarna; Hasan Mahmudul; Hyok Ra Song (Goodwood Publishing, 2025)
Purpose: This research aims to examine the impact of academic stress on the psychological well-being of international students at Northeast Normal University. By analyzing stressors such as academic workload, language barriers, and cultural adjustments, the research seeks to understand how these factors contribute to anxiety and overall mental health. Methods: A quantitative correlational design was employed focusing on international students at Northeast Normal University, China. Using the Perception of Academic Stress (PAS) Scale and the Psychological Well-Being (PWB) Scale, data were collected from 80 respondents (40 males and 40 females) through a Google Form questionnaire. SPSS was used for descriptive, correlation, and regression analyses to determine the relationship between academic stress dimensions—academic expectation, examination, and self-perception—and psychological well-being. Results: The findings reveal that both academic stress and psychological well-being are moderately high among international students, with academic stress explaining 43.1% of the variance in psychological well-being. Self-perception emerged as the most significant predictor, emphasizing its critical role in stress management and mental health. No significant gender differences were found, but age showed a significant relationship with academic stress. Conclusion: Academic stress significantly affects the mental health of international students, with self-perception playing a vital role in coping. Institutions should prioritize interventions that enhance self-awareness and psychological resilience. Limitations: The study focuses on one institution with a limited sample, restricting generalizability. Contribution: The study offers empirical insights into academic stress predictors and supports universities in designing culturally sensitive mental health and academic support programs for international students.